Analisis Implementasi Mobile E-Samsat Delivery dalam Peningkatan Pembayaran Pajak Kendaraan dan Pendapatan Asli Daerah di Kabupaten Sumbawa - Masriki Masriki; Muhamad Hidayat (SENTRI: Jurnal Riset Ilmiah, 2026)
Motor vehicle tax is an important source of Regional Original Revenue (PAD), but the increase in the number of vehicles in Sumbawa Regency has not been matched by taxpayer compliance. The government has introduced digital innovations such as SIGNAL and E-Samsat Delivery to facilitate tax payments and improve services. Previous research results show that the effectiveness of these innovations is still varied. Therefore, this study aims to analyze the impact of implementing a digital tax payment application on the increase in motor vehicle tax payments and PAD in Sumbawa Regency. This study uses a qualitative method with a descriptive approach and case study strategy to gain an in-depth understanding of the implementation of the E-Samsat Delivery application in increasing motor vehicle tax payments in Sumbawa Regency. This approach was chosen because it can delve into the experiences, perceptions, and views of the Head of Samsat, managing staff, and taxpayers thru observation, interviews, and documentation. Additionally, this research uses the Technology Acceptance Model (TAM) framework to analyze perceptions of ease, usefulness, attitude, and intention to use the application. The research results show that Mobile E-Samsat Delivery facilitates vehicle tax payments and has the potential to increase taxpayer compliance. However, its contribution to increasing PAD is not yet optimal because the number of users and service uptake has decreased. Based on the analysis of the Technology Acceptance Model (TAM), perceived usefulness is the most influential factor in the acceptance of the application, followed by perceived ease of use, positive attitude, and the community's intention to use the service. The success of the implementation still requires improvements in socialization, digital literacy, and service quality.